The Genesis of the International Criminal Court - Huzik, Oleksandra (Journal of Legal Studies, 2021)
This work analyzes the practice of the International Criminal Court (ICC) as the most ambitious project aimed at combating and preventing mass violations of human rights in inter-and intrastate conflicts. Sure thing, such an institution has not emerged from anywhere, but it is the culmination in the progress of international criminal law evolution. That is why the progress that was made over the centuries and historical conditions forcing its establishment cannot be ignored. This article studies the formation of the International Criminal Court through the prism of the history of previous models of judicial bodies bringing to justice war criminals. Moreover, it analyses the historical conditions and international debates around the establishment of a permanent international criminal court.  Conclusions focus on the problems that arose during the establishment of the ICC, and the ways in which they affect ICC activities nowadays.